2023
DOI: 10.3390/agronomy13092289
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hydrological Conditions and Driving Factors Analysis of the Yongding River in a Changing Environment: A Case Study of the Xiangshuipu Section

Yiyang Yang,
Siyu Cai,
Hao Wang
et al.

Abstract: Hydrological conditions are key factors in the evaluation of water resources and ecosystems. The Yongding River Basin has many irrigated areas, and excessive agricultural water consumption has led to serious water shortages and ecosystem damage. To investigate the evolution of ecohydrological conditions and their driving factors in the Yongding River basin in a changing environment, this study combines indicators of hydrologic alteration with the range of variability approach (IHA-RVA) to identify the most eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Yang et al [13] focused on the Yongding River Basin, specifically examining the Xiangshuipu section, to unravel the evolution of hydrological conditions and their driving forces. Employing a combination of the Indicators of Hydrologic Alteration (IHAs), the Range of Variability Approach (RVA), and the WetSpa model, their study identified key hydrological indicators and quantified the contributions of climate change, reservoir storage, and irrigation practices to hydrological alterations.…”
Section: The Relationship Between Hydrological Conditions and Human A...mentioning
confidence: 99%
“…Yang et al [13] focused on the Yongding River Basin, specifically examining the Xiangshuipu section, to unravel the evolution of hydrological conditions and their driving forces. Employing a combination of the Indicators of Hydrologic Alteration (IHAs), the Range of Variability Approach (RVA), and the WetSpa model, their study identified key hydrological indicators and quantified the contributions of climate change, reservoir storage, and irrigation practices to hydrological alterations.…”
Section: The Relationship Between Hydrological Conditions and Human A...mentioning
confidence: 99%